2013
DOI: 10.1253/circj.cj-13-0089
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of and Risk Factors for Reoperation After Mitral Valve Repair for Degenerative Mitral Regurgitation

Abstract: Background:We reviewed our 20-year experience of mitral valve (MV) repair for degenerative mitral regurgitation (MR) and analyzed the mechanisms and risk factors of reoperation. Methods and Results:Six hundred and fifty-four patients who underwent MV repair for degenerative MR between 1991 and 2010 were retrospectively reviewed. The mean follow-up duration was 7.5±4.9 years. Late echocardiography was obtained at a fixed schedule. Standard procedures for MV repair were resection and suture for posterior prolaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In the reoperation group, the patients with mild residual MR before discharge usually had technical issues that affected early-term outcomes. In contrast, the patients who underwent relatively late reoperation because of progression of degenerative changes did not have mild residual MR. Murashita et al [12] also showed that the cause of recurrent MR affected the time of reoperation, indicating that early reoperation was associated with technical issues and that late reoperation was related to progression of degenerative change. In contrast, among patients who had moderate to severe recurrent MR with mild residual MR before discharge without technical issues, few patients had indications for reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…In the reoperation group, the patients with mild residual MR before discharge usually had technical issues that affected early-term outcomes. In contrast, the patients who underwent relatively late reoperation because of progression of degenerative changes did not have mild residual MR. Murashita et al [12] also showed that the cause of recurrent MR affected the time of reoperation, indicating that early reoperation was associated with technical issues and that late reoperation was related to progression of degenerative change. In contrast, among patients who had moderate to severe recurrent MR with mild residual MR before discharge without technical issues, few patients had indications for reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous studies demonstrate a persistent failure rate after repair inherently related to the inability of surgery to correct the underlying disease process. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] The Brigham and Women's Hospital group reported a 20-year incidence of mitral reoperation of 18%, whereas the Toronto group reported a reoperation rate of only 5.9%. 6 Recurrence of moderate-to-severe MR at 20 years in the latter study was 30.8%, whereas the Mayo clinic group recently reported a 15-year incidence of significant recurrent MR of 13.3%.…”
Section: See Editorial Commentary Page 831mentioning
confidence: 99%
“…Although mitral valvuloplasty is a well established procedure for MR (Lazam et al, 2017), there have also been reports of recurrent MR requiring repeated mitral valve surgery after an initial mitral valvuloplasty (Nishida et al, 2018;Murashita et al, 2013). In this study, we observed the structural properties of ruptured chorda tendineae by evaluating tissue density.…”
Section: Figurementioning
confidence: 97%
“…However, even when the anatomy of the mitral valve complex inside the heart has been established, the association with the structural properties and the rupturing of chordae tendineae has not been fully investigated. Therefore, there is a possibility of a recurrence of MR following conventional mitral valve repair (Nishida et al, 2018;Murashita et al, 2013).…”
Section: Introductionmentioning
confidence: 99%